Freedom Fighter Articles & Essays - - (Bridge Publications, 2012)
Presenting forty-four essays, Freedom Fighter is L. Ron Hubbard’s long and unblinking look at precisely what plagues 21st century Earth—the whys, wherefores, and what we can do about it. Included is Mr. Hubbard’s incisive essay, “Strong Voices in the Land.”